PENGARUH AUDIT TENURE, OPINION SHOPPING, LEVERAGE DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2017 - Elva Yuli Ariska; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTThis research aims to analyze the Effect of Audit Tenure, Opinion Shopping, Leverage and Growth of the Company on Disclosure of Going Concern Audit Opinion. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange 2015 - 2017. The sampling technique in this study used Purposive Sampling and produced as many as 50 companies into the research sample. The analytical method used is Logistic Regression with SPSS 22 For Windows Software. Based on the results of the analysis, the following conclusions are obtained: Test the independent variables simultaneously using the omnibus test shown in table 4.8 proving that the independent variables in the study are audit tenure, opinion shoping, leverage and company growth simultaneously influence the acceptance of opinion audit going concern. The partial test results show that audit tenure, opinion shopping and leverage have an effect on the audit going concern while the company's growth has no effect on audit going concern. This research is expected to be a consideration for future researchers to conduct similar research and for investors as a consideration in decision making related to economic benefits in the future also in maintaining, continuing and developing business planning.Keywords: Audit tenure, opinion shopping, leverage, company growth, Audit going concern.